If you build it, promote it, and they trust you, then they will come: Diffusion strategies for science gateways and cyberinfrastructure adoption to harness big data in the science, technology, engineering, and mathematics (STEM) community - Kerk F. Kee; Bethanie Le; Kulsawasd Jitkajornwanich (Concurrency and Computation Practice and Experience, 2021)
Abstract In the big data era, for science gateways (SG) and cyberinfrastructure (CI) projects to have the greatest impacts, they need to be widely adopted in the scientific community. However, diffusion activities, or activities aimed to spread SG/CI in the science, technology, engineering, and mathematics community, are often an afterthought in projects. We warn against the fallacy of “If You Build It, They Will Come .” Projects could be intentional in promoting tool adoption. Based on an analysis of 83 interviews with 66 administrators, developers, scientists/users, and outreach educators of SG/CI, we identified seven external communication practices—raising awareness, personalizing demonstrations, providing online and offline training, networking with the community, building relationships with trust, stimulating word‐of‐mouth persuasion, and keeping reliable documentation. With these strategies, we revised the pop culture line to “If You Build It, Promote It, and They Trust You, Then They Will Come.” We also observed the beliefs that external communication is mainly necessary when seeking continuous funding, and it belongs to the skillset of nontechnical staff. These two beliefs may explain why external communication is underemphasized in many SG/CI projects. The article serves as evidence to justify a bigger budget in funding proposals for diffusion strategies to increase adoption and broader impacts.
Keywords: Scientific Computing and Data Management; Research Data Management Practices; scientometrics and bibliometrics research